2013
DOI: 10.3389/fneur.2013.00032
|View full text |Cite|
|
Sign up to set email alerts
|

Matrix Metalloproteinases and Blood-Brain Barrier Disruption in Acute Ischemic Stroke

Abstract: Ischemic stroke continues to be one of the most challenging diseases in translational neurology. Tissue plasminogen activator (tPA) remains the only approved treatment for acute ischemic stroke, but its use is limited to the first hours after stroke onset due to an increased risk of hemorrhagic transformation over time resulting in enhanced brain injury. In this review we discuss the role of matrix metalloproteinases (MMPs) in blood-brain barrier (BBB) disruption as a consequence of ischemic stroke. MMP-9 in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
243
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(253 citation statements)
references
References 160 publications
4
243
0
6
Order By: Relevance
“…In these sequential reactions, ROS is thought to affect the signaling pathways that induce the expression and activation of MMPs directly and/or indirectly (Jian Liu et al, 2005). Among MMPs, MMP-9 is relavant to BBB disruption, leading to increased vascular permeability and extravasation of plasma and blood cells, and finally resulting in severe brain edema and hemorrhagic transformation (Lakhan et al, 2013). A well-designed study with MMP-9-/-mice and chimeric mice with either MMP-9-deficient or MMP-9-containing leukocytes clearly demonstrated that MMP-9 released from neutrophils promoted further recruitment of neutrophils and caused BBB disruption secondary to collagen IV degradation (Gidday et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In these sequential reactions, ROS is thought to affect the signaling pathways that induce the expression and activation of MMPs directly and/or indirectly (Jian Liu et al, 2005). Among MMPs, MMP-9 is relavant to BBB disruption, leading to increased vascular permeability and extravasation of plasma and blood cells, and finally resulting in severe brain edema and hemorrhagic transformation (Lakhan et al, 2013). A well-designed study with MMP-9-/-mice and chimeric mice with either MMP-9-deficient or MMP-9-containing leukocytes clearly demonstrated that MMP-9 released from neutrophils promoted further recruitment of neutrophils and caused BBB disruption secondary to collagen IV degradation (Gidday et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“… ðåçóëüòàòå ýòîãî â àñòðîãëèè àêòèâè-ðóþòñÿ âíóòðèêëåòî÷íûå ïðîöåññû, ñâÿçàííûå ñ óâå-ëè÷åíèåì óðîâíÿ êàëüöèÿ â öèòîçîëå, à òàêaeå ôåðìåí-òû, ó÷àñòâóþùèå â ïðîäóêöèè ñâîáîäíûõ ðàäèêàëîâ è â çàùèòå êëåòîê îò íèõ [17,33]. Áëàãîäàðÿ òåñíîìó ôóíêöèîíàëüíîìó ñîïðÿaeåíèþ àñòðîöèòîâ è ýíäîòå-ëèîöèòîâ ýòè ñîáûòèÿ ïðèâîäÿò ê èçìåíåíèþ ïðîñâåòà è ïðîíèöàåìîñòè êàïèëëÿðîâ ãîëîâíîãî ìîçãà, íàðó-øåíèþ ïëîòíûõ è ùåëåâûõ êîíòàêòîâ, íàðóøåíèþ ôóíêöèîíèðîâàíèÿ òðàíñïîðòíûõ ñèñòåì â êëåòêàõ öåðåáðàëüíîãî ýíäîòåëèÿ, ÷òî ñîïðîâîaeäàåòñÿ óâåëè-÷åíèåì âíåêëåòî÷íîé ïðîòåîëèòè÷åñêîé àêòèâíîñòè, ïîâðåaeäåíèåì ñòðóêòóðû ýêñòðàöåëëþëÿðíîãî ìàò-ðèêñà è êëåòîê ýíäîòåëèÿ è àñòðîãëèè [42,79].…”
Section: íàðóøåíèÿ ñòðóêòóðíîé è ôóíêöèîíàëüíîé öåëîñòíîñòè ãåìàòîýíöunclassified
“…Èõ ôèçèîëîãè-÷åñêàÿ ðîëü ðàçíîîáðàçíà: ó÷àñòèå â àíãèîãåíåçå, ðå-ìîäåëèðîâàíèè òêàíåé, ðåãóëÿöèè êëåòî÷íîé ïðîëè-ôåðàöèè, ìèãðàöèè, äèôôåðåíöèðîâêè è àïîïòîçà. Îíè çàäåéñòâîâàíû â ïðîòåîëèçå ìåìáðàííûõ ðåöåï-òîðîâ, àêòèâàöèè è äåàêòèâàöèè õåìîêèíîâ è öèòîêè-íîâ [42].…”
Section: ìîëåêóëû ñ ôåðìåíòàòèâíîé ïðîâîñïàëèòåëüíîé àêòèâíîñòüþunclassified
“…Although the catalytic domain of MMPs is structurally similar, there are many differences in substrate specificity, cellular and tissue localization, membrane binding and regulation, making this a versatile family of enzymes with a multitude of physiological functions, which are not fully understood. Essentially, all members of the MMP family have been linked to disease development, notably to cancer metastasis, chronic inflammation with ensuing tissue damage, as well as to neurological disorder [32]. MMPs activity is regulated by a group of endogenous proteins called tissue inhibitor of metalloproteinases (TIMPs), which bind to active and alternative sites of activated MMPs [33].…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%